Influence of Access and Space Appearance on Comfort for Users in Alun-Alun Gianyar - Saputra, Kadek Edi; Dharmadiatmika, I Made Agus; Fitriana, Devvy Alvionita; Megisterina (Institute for Research and Community Services Udayana University, 2026)
Green open spaces (RTH) play a crucial role in maintaining ecological balance and improving the quality of life for urban residents. One of the primary typologies of RTH is the city park, functionally represented by Gianyar City Square as a center for sports, recreation, social interaction, and art performances. Following the revitalization program, significant transformations in accessibility and visual aesthetics have occurred, creating an urgent need to assess their impact on visitor comfort. This study aims to analyze the influence of accessibility and spatial appearance variables on user comfort levels in Gianyar City Square. The methodology used was a quantitative approach, involving 100 respondents selected through a specific sampling technique. Primary data were collected through a structured questionnaire and then processed using parametric statistical analysis, including validity tests, reliability tests, and classical assumption tests (normality and heteroscedasticity). Hypotheses were tested through linear regression analysis, supported by F-tests and T-tests. The results indicate that access and spatial appearance variables simultaneously and partially have a positive and significant effect on user comfort. Empirical findings identified that the spatial appearance variable was the most dominant determinant with an influence coefficient of 0.7. This indicates that visual aesthetics and spatial arrangement post-revitalization are key factors in enhancing the spatial experience and psychological comfort of visitors.